Role of vitamin D in the pathogenesis of early-onset preeclampsia: a narrative review - Zheng, Shu; Dong, Shuai; Shen, Huimin; Xu, Peng; Shu, Chang (Frontiers in Nutrition, 2025)
Early-onset Preeclampsia (EOPE) is a severe pregnancy complication that poses significant risks to both maternal and fetal health, often leading to fetal growth restriction and maternal morbidity. Despite extensive research, the etiology of EOPE remains unclear, though emerging evidence suggests that vitamin D (VD) may play an important role in placental development and function. Recent studies associate VD deficiency with adverse pregnancy outcomes, including EOPE, through mechanisms such as impaired trophoblast invasion and immune dysregulation at the maternal-fetal interface. This review aimed to synthesize current literature on the role of VD in the pathogenesis of EOPE. We reviewed in vitro, in vivo, and clinical studies to evaluate the impact of VD on immune modulation, angiogenesis, oxidative stress, and trophoblast migration and invasion in the placenta. This comprehensive review aims to provide insights into how VD deficiency exacerbates placental dysfunction, contributing to the development of EOPE. These insights support the rationale for VD supplementation as a potential preventive strategy and highlight the need for further clinical investigation.